(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
PIRLS international reading literacy assessment programmed working with text in this article is on increasing the level of data was causing, then covers the aspects of literacy and then also through the internet site gipermatn applied to the texts of dynamic text and mentioned by many similar texts